EFFECT OF SEAWEED EXTRACT AND ATONIC SPRAY ON SOME PHYSICAL AND CHEMICAL CHARACTERISTICS OF (MORINGA OLEIFERA) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The experiment was conducted at a research station affiliated with the Ministry of Agriculture during the 2023-2024 fall season. We used a randomized complete block design (RCBD) and compared treatment means using the Least Significant Difference (LSD) test at a 0.05 probability level. Moringa oleifera trees were treated with auxin amino acid and seaweed extract. The experiment consisted of two factors and three replicates, examining the interaction between auxin and seaweed extract at concentrations of 0-, 1-, and 2-ml L-1. Plants were sprayed three times at 10-day intervals. This study aimed to investigate the effects of auxin and seaweed extract on some physical and chemical properties of Moringa oleifera and identify the optimal concentration for best results in the southern region, particularly in Dhi Qar Governorate. The results can be summarized as follows: Foliar application of auxin significantly affected some vegetative growth traits and chemical characteristics in leaves, with the highest values recorded for stem diameter, plant height, number of leaves, chlorophyll content, carotenoids, and carbohydrates, which were (0.611 and 96.39) cm plant-1, (242.3 leaves plant-1), and (0.541, 27.203, and 83.39) mg 100g-1, respectively. Seaweed extract fertilization showed a significant effect on some vegetative growth traits and chemical characteristics in leaves, with the highest values recorded for stem diameter, plant height, number of leaves, chlorophyll content, carotenoids, and carbohydrates, which were (0.617 and 96.83) cm plant-1, (231.2 leaves plant-1), and (0.560, 29.108, and 85.30) mg 100g-1, respectively. The interaction between auxin and seaweed extract had a significant effect on some vegetative growth traits and chemical characteristics, particularly in the number of leaves, chlorophyll content, carotenoids, and carbohydrates, which recorded (296.5 leaves plant-1), (0.632, 36.437, and 88.84) mg 100g-1, respectively.